Monographia Indicorum Fimbristylium Praecursores - Novelties in Fimbristylis Vahl – II - Govindarajalu , E. (Rheedea, 1997)
Six new species of Fimbryistylis, viz., F. benthamiana, F. humerosa, F. ultragluma, F. dimorphonucifera, F. mycosa and F. pandurata are described and illustrated.